123k views
11 votes
Find the statement Pk + 1 for the given statement Pk

Find the statement Pk + 1 for the given statement Pk-example-1
User Irene
by
4.9k points

1 Answer

8 votes

Explanation:

k has to be replaced by k+1.

so,

4 / ((k+1)(k+1 + 3)) = 4 / ((k+1)(k+4))

I am not sure how far your teacher expects you to go with this.

just in case, I will do also the full multiplications

4 / ((k+1)(k+4)) = 4 / (k² + 4k + k + 4) = 4 / (k² + 5k + 4)

and if you need the factor to go from Pk to Pk+1 :

Pk+1 / Pk = (4/((k+1)(k+4))) / (4/(k(k+3)) =

= (4/((k+1)(k+4))) × (k(k+3))/4 =

= (k(k+3)) / ((k+1)(k+4))

User Adam Winter
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.